Case Report of Subdural Hematoma in a Patient With Sturge–Weber Syndrome and Literature Review: Questions and Implications for Therapy. (May 2013) - Lopez, Jonathan; Yeom, Kristen W.; Comi, Anne; Van Haren, Keith
Sturge–Weber syndrome is a neurocutaneous disorder associated with vascular abnormalities in the skin, eye, and brain leading to both acute and chronic cerebral hypoperfusion and, in some affected children, brain injury. Aspirin can reduce stroke-like events and seizure episodes and prevent further brain injuries in these patients. Although a few cases of intracranial hemorrhage in patients with Sturge–Weber syndrome have been reported, prior reports have not discussed this complication with regard to particular therapies. The authors present a toddler with Sturge–Weber syndrome who developed a subdural hematoma in the setting of a mechanical fall with minor head trauma. They discuss the possible role of aspirin in contributing to, or perhaps protecting against, intracranial hemorrhage in patients with Sturge–Weber syndrome. Further data are needed to establish the utility of aspirin in Sturge–Weber syndrome.